Effectiveness of storytelling and roleplay in improving oral hygiene knowledge and supporting nutritional health among elementary school students: A quasy experimental study - Anses Warman; Arnetty Arnetty; Ika Ifitri; Fadila Rahmat Dinanti; Amiruddin Amiruddin; Renita Eka Zurianti (AcTion: Aceh Nutrition Journal, 2025)
Poor oral hygiene among school-aged children can compromise food intake and contribute to nutritional problems including stunting, wasting, and underweight. However, few studies have explored active learning methods that integrate oral health education with its nutritional implications. This study evaluated the effectiveness of storytelling and roleplay in improving oral hygiene knowledge and their potential relevance to nutritional health promotion. A true experimental study with a pretest-posttest design on two intervention groups was conducted in December 2024 at State Elementary School 23, Kubang Putiah, Agam Regency, West Sumatra. Thirty-six students in grades III and IV were randomly assigned to either the storytelling or roleplay groups. Both groups received one week of structured counseling. Instrument validity and reliability were confirmed through expert review and Cronbach’s alpha testing (α > 0,80). Paired and independent t-tests were used at the 95% confidence level. Results indicated significant post-intervention knowledge gains in both groups (p < 0,001), with the roleplay group achieving a greater mean improvement (27,8 ± 1,77) than the storytelling group (19,5 ± 2,60; p < 0,001). Roleplay demonstrated superior effectiveness in enhancing children’s oral health literacy, which is essential for supporting school-based malnutrition prevention initiatives such as the School Health Unit (SHU) program and curriculum integration. Longitudinal studies are recommended to examine behavioral changes and their measurable impact on nutritional status.